TINJAUAN UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS TERHADAP PERANAN NOTARIS DALAM PEMBAGIAN HARTA WARISAN SECARA TESTAMENTER - Rodiansyah Rodiansyah (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTSomeone to be able to inherit under the law of inheritance west known presence of 2 ways inherited based on the Act (Ab Intestato) and inherit based on a will (Ad Testamato). Testamentary inheritance problems with deed (acte testament) has been around a long time, on the last will or testament deed (acte testament) in general is a statement from someone before she died and carried out after death. Creating a testament deed (acte testament) is a legal act, of a person who acts against the legacy assets after he died, so in making a will is a legal act unilaterally in this case very closely connected with nature